King and Kayla and the case of the missing dog treats - Butler, Dori Hillestad (Butler, Dori Hillestad. King & Kayla, 2017)
King's human, Kayla, has baked some treats for a friend's new puppy, Thor, but some go missing and it is up to King to find the culprit.